THU0210 RNA-SEQ REVEALS THE MECHANISM OF THALIDOMIDE IN LUPUS CUTANEOUS LESIONS. (June 2019) - Solé-Marcé, Cristina; Alvarez-Rios, Ana Maria; Moline, Teresa; Ferrer, Berta; Ordi-Ros, Josep; Cortés-Hernández, Josefina
Abstract : Background: Cutaneous Lupus Erythematosus (CLE) is common, largely heterogeneous and characterized by a chronic relapsing course. As many as 70 to 80% of patients with SLE will develop skin lesions at some point during the course of their disease, with a significant proportion being disfiguring and debilitating [1]. Conventional therapy consists of topical steroids and antimalarial agents but ∼40% of patients will be refractory to this regimen [2]. Thalidomide has been the only one that has shown an effectiveness of 90% [3], however, its mechanism of action in the disease is not known at all. In addition, its use is limited due mainly to its side effects such as teratogenicity and the development of peripheral polyneuropathy. Objectives: Identification of the possible mechanisms of thalidomide in cutaneous lupus erythematosus. Methods: Skin biopsies before and during treatment has been performed on a cohort of CLE patients treated (N=20) and not treated with thalidomide (N=5). Through a differential study of gene expression with RNA-seq and its subsequent validation, the mechanism of thalidomide action has been identified. The cell population in the tissue and in the blood of the patients and their evolution due to the treatment has also been studied by flow cytometry. In vitro experiments using isolated lupus cutaneous lymphocyte and keratinocytes has been performed to see the specific biological effect of thalidomide (Figure 1 ). Results: Flow cytometry of immune cells from blood obtained pre- and post-treatment revealed a significant activation of Thelper (p<0.001), a differentation towards Th2 subpopulation and an increase of natural killer after thalidomide effect. Not significant difference were observed in macrophages and dendritic cell. In addition, after RNA-seq analysis two fundamental molecular pathways has been identified in responder thalidomide treatment patients: 1) via IRF4-NFκβ pathway modulation. 2) via AMPK-mTOR pathway modulation. In vitro experiments using isolated primary cells from lupus cutaneous patients demostrated that thalidomide modulate IRF4 in lymphocytes to inhibite NFκβ pathway; however, AMPK-mTOR pathway is inhibited in keratinocytes by thalidomide effect. Conclusion: Taken together, we show that mechanism of thalidomide in CLE is dual. It might inhibited NFκβ pathway by modulation of IRF4 in lymphocyte but, in the same time, might inhibited MTOR pathway by modulation of AMPK in keratinocytes. References: [1] Henry J. Lee, et al. Cutaneous lupus erythematosus: Understanding of clinical features, genetic basis, and pathobiology of disease guides therapeutic strategies. Autoimmunity 2006; 39(6): 433–444. [2] Callen JP. Update on the management of cutaneous lupus erythematosus. Brit J Dermatol 2004; 151: 731-736. [3] Cortés-Hernández J, et al. Thalidomide in the treatment of refractory cutaneous lupus erythematosus: prognostic factors of clinical outcome. Br J Dermatol. 2012; 166(3):616-23. Acknowledgement: This work was financed by Instituto de Salud Carlos III (Spain Government, PI15/02145), Catalan Lupus Foundation and A.Bosch Foundation. Disclosure of Interests: Cristina Solé-Marcé: None declared, Ana Maria Alvarez-Rios: None declared, Teresa Moline: None declared, Berta Ferrer: None declared, Josep Ordi-Ros: None declared, Josefina Cortés-Hernández Grant/research support from: GSK, Speakers bureau: GSK